Online Hostel Mawar application / Harlina Zaini - Zaini, Harlina (Faculty of Information Technology and Quantitative Sciences, 2005)
With the fast technology enhancement, there are many current manual applications can be migrated to web-based applications and assist the university's personnel in carrying out of their daily routine tasks. Hostel application is one of the processes for the students in order to stay in. The hostel management need to process the application manually and then come out with the result. The result of the application is normally sent through the conventional mail, which can result in late delivery or even failure of delivery. By implementing an on-line hostel application, it will definitely reduce some of the manual process for administration. The student might access their application result anytime and anywhere through web-based applications. In the process of developing online hostel application, certain data were gathered from various sources such as from college's staffs, personnel from HEP (students' affair unit), fellow students and self experience. Other fact findings were made by studying existing manual college application process, application forms, from mySQL manual and PHP manual for developing the system. From the findings, some recommendation can be made such as implementation of the system made through web so that the student can access it through internet. With the implementation through web based system, it is hope that the system will not only help in the college's application's process and storing the data but also to cultivate the migration of manual process to automate process especially using the web based application.